Characterization of metallic interconnects extracted from Solid Oxide Fuel Cell stacks operated up to 20, 000 h in real life conditions: The fuel side. (6th July 2021) - Ghiara, Giorgia; Piccardo, Paolo; Bongiorno, Valeria; Repetto, Luca; Geipel, Christian; Spotorno, Roberto
Abstract: The performance of an SOFC stack is related to the evolution over time of the materials during operation. Metallic interconnects (MICs) are exposed to high temperature (ca. 850 °C) and dual atmosphere (fuel and air streams), and hence react to form an oxide scale on top. This paper focuses on the fuel side of the MIC and investigates the nature of the oxides formed in SOFC stacks field operated by the SUNFIRE GmbH Company for up to 20, 000 h in the frame of the EU-H2020 ADASTRA project. This opportunity supports the understanding on how the metal (i.e., CROFER®22APU) reacts once exposed to the fuel stream by performing investigations on the surface and on the cross-section of the samples by SEM-EDS and micro-Raman spectroscopy. The results show the presence of a layered thermally grown oxide (TGO) rich in Cr at the interface with the metal. On top of the scale, a predominant presence of Mnx Oy is found supporting the hypothesis of a further reaction of the TGO with selective Cr depletion. The manganese oxides may represent a severe issue due to their very low conductivity. Highlights: Interconnects oxidize when exposed to wet fuel in field operated SOFC stack. The pH2 O/pH2 ratio affects the oxide formation. The thermal gradient between fuel Inlet and Outlet positions affects the oxide growth rate. Mnx Oy formed on top represents a potential issue for stack performances due to its low conductivity.